2000
DOI: 10.1056/nejm200009073431003
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Inhaled Fluticasone and Oral Prednisone for Children with Severe Acute Asthma

Abstract: Children with severe acute asthma should be treated with oral prednisone and not with inhaled fluticasone or a similar inhaled corticosteroid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
2
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(113 citation statements)
references
References 33 publications
2
102
2
7
Order By: Relevance
“…15 However, two studies demonstrated that improvement in measures of pulmonary function was more rapid among children who receive systemic corticosteroids. 17,18 Although these metaanalyses 15,16 indicate no evidence of difference in the clinical efficacies of systemic and ICSs, limitations of the studies which comprise the metaanalyses, predominantly relatively small sample sizes, temper these findings and provide insufficient evidence at the present time to recommend the routine use of high-dose ICS as an alternative to systemic corticosteroids in children presenting to ED with acute exacerbations of asthma. However, in milder episodes, high-dose ICS therapy may be an acceptable alternative to systemic corticosteroids.…”
Section: Inhaled Corticosteroidsmentioning
confidence: 97%
“…15 However, two studies demonstrated that improvement in measures of pulmonary function was more rapid among children who receive systemic corticosteroids. 17,18 Although these metaanalyses 15,16 indicate no evidence of difference in the clinical efficacies of systemic and ICSs, limitations of the studies which comprise the metaanalyses, predominantly relatively small sample sizes, temper these findings and provide insufficient evidence at the present time to recommend the routine use of high-dose ICS as an alternative to systemic corticosteroids in children presenting to ED with acute exacerbations of asthma. However, in milder episodes, high-dose ICS therapy may be an acceptable alternative to systemic corticosteroids.…”
Section: Inhaled Corticosteroidsmentioning
confidence: 97%
“…Patients treated with fluticasone via metered-dose inhaler, exhibited a worse response to treatment when compared with those who were prescribed oral prednisone. 29 After 4 hours of treatment there was a 9.4% increase in FEV 1 in the fluticasone group and of 18.9% in the prednisone group after 4 hours de treatment.…”
Section: Discussionmentioning
confidence: 82%
“…Maintenance doses of ICS should be continued or started as soon as possible to form the basis of the chronic asthma management plan, and to allow the educational process regarding controller therapy to start even while the patient is hospitalised. [6,[44][45][46][47][48] …”
Section: Inhaled Steroids (Ics)mentioning
confidence: 99%